Milk Inhibits the Biological Activity of Ricin - Rasooly, Reuven (American Society for Biochemistry and Molecular Biology, 2012)
Ricin is a highly toxic protein produced by the castor plant Ricinus communis. The toxin is relatively easy to isolate and can be used as a biological weapon. There is great interest in identifying effective inhibitors for ricin. In this study, we demonstrated by three independent assays that a component of reconstituted powdered milk has a high binding affinity to ricin. We discovered that milk can competitively bind to and reduce the amount of toxin available to asialofetuin type II, which is used as a model to study the binding of ricin to galactose cell-surface receptors. Milk also removes ricin bound to the microtiter plate. In parallel experiments, we demonstrated by activity assay and by immuno-PCR that milk can bind competitively to 1 ng/ml ricin, reducing the amount of toxin uptake by the cells, and thus inhibit the biological activity of ricin. The inhibitory effect of milk on ricin activity in Vero cells was at the same level as by anti-ricin antibodies. We also found that (a) milk did not inhibit ricin at concentrations of 10 or 100 ng/ml; (b) autoclaving 10 and 100 ng/ml ricin in DMEM at 121 °C for 30 min completely abolished activity; and (c) milk did not affect the activity of another ribosome inactivating protein, Shiga toxin type 2 (Stx2), produced by pathogenic Escherichia coli O157:H7. Unlike ricin, which is internalized into the cells via a galactose-binding site, Stx2 is internalized through the cell surface receptor glycolipid globotriasylceramides Gb3 and Gb4. These observations suggest that ricin toxicity may possibly be reduced at room temperature by a widely consumed natural liquid food.